Identifikasi Bacillus sp. pada Fermentasi Tapai Singkong - Saridewi, Uut; Kundera, I Nengah; Budiarsa, I Made; Nurdin, Musdalifah; Trianto, Manap; Windarsih, Yulia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify Bacillus sp. in cassava tapai fermentation that has potential as a probiotic ingredient. The type of research used is descriptive exploratory using the Standard Plate Count (SPC) method, Gram staining, and biochemical testing with the Microbant System 12B. Cassava tapai samples were obtained by fermenting them for 5 days. Fermentation of cassava tapai was carried out in the Biology Education Laboratory. The results of the study showed that (1) The Standard Plate Count test yielded the highest value on the 4th day of observation at 231x10-2 CFU/ml, while the lowest value was observed on the 1st day at 162x10-2 CFU/ml. (2) Gram staining of the bacterial isolates revealed Gram-positive rod-shaped morphology. (3) Biochemical testing using the Microbant System 12B showed the ability to ferment several types of carbohydrates such as sorbitol, sucrose, lactose, arabinose, adonitol, and salicin, but it cannot ferment inositol, malonate, rhamnose, raffinose, and arginine. Thus, it can be concluded that the bacteria identified from cassava tapai fermentation can ferment in accordance with the physiological capabilities of Bacillus sp.